From Environmental Imperialism To Cultural Imperialism - Dr. Zakia Arar (Elementary Education Online, 2024)
This study seeks to present and discuss ecology in a post-colonial cognitive context, as the research presents the concept of environmental imperialism as an expression of the exploitation of the environment by colonial powers and making it a tool to impose their hegemony over Third World countries. It explains how developed countries exploited environmental resources in colonies and transferred polluting industries and toxic waste to them, which led to the deterioration of their environment and the spread of diseases among their populations. The research also discusses the impact of environmental hegemony on thought and culture, and thus produced perceptions that serve the control of the West and perpetuate the dependence of developing countries, which confirms that the impact of environmental imperialism is not limited to nature as much as it extends to thought as well. This calls for the necessity of awareness of its dimensions to confront its effects